Penerapan Model PBL Berbantuan Lembar Ceria untuk Meningkatkan Minat Belajar pada Murid SD Kelas Rendah - Affan Zaimul Umam; Panca Dewi Purwati (ALSYS, 2026)
Fluctuations in learning outcomes resulting from low interest in conventional Bahasa Indonesia instruction at the primary level remain a problem that has not been specifically examined in depth, even though student engagement and consistency of achievement have been widely discussed in previous studies. This study aimed to increase learning interest and stabilize students’ learning outcomes through the implementation of a Problem-Based Learning (PBL) model supported by the Lembar Kerja Murid (LKM) “Lembar Ceria” worksheet. A Classroom Action Research approach with a collaborative design was applied to 28 second-grade students at SDIT Insan Mulia. Data were collected through classroom observations, document analysis of students’ work, and written tests, and were analyzed using comparative descriptive techniques. The results show that the use of the Lembar Ceria worksheet within a PBL framework successfully increased learning interest, as reflected in students’ task commitment reaching 100%, and stabilized as well as improved learning outcomes, indicated by an increase in the class mean score from 64.80 (pre-cycle) to 84.71 (Cycle I), with a classical mastery level of 86.53%. These findings contribute to strengthening the theoretical framework of media-assisted active learning and broaden understanding of effective teaching strategies at the elementary level. The study concludes that visually engaging worksheets combined with PBL syntax play a crucial role in creating an enjoyable and meaningful learning atmosphere, and recommends that educators adopt visually stimulating worksheets to enhance student engagement. The implications include a theoretical contribution to the literature on PBL and practical recommendations for elementary school teachers, while also opening avenues for further research on the use of similar media in other subjects to promote more holistic stability in learning outcomes.